'Give us back our eleven days': Brexit or Breaksit?. Issue 1 (March 2020) - Hobson, Marian
Abstract : A major adjustment to the British calendar occurred in 1752. This was the passage from the Julian calendar to the Gregorian, inaugurated in the sixteenth century by command of Pope Gregory XIII in the papal dominions, and swiftly followed by much of the rest of Europe. The consequent loss of eleven days in the 'new style' British calendar seems to have provoked a riot. The alternative calendars had been the source of complication in trade and trade agreements and had led to friction in everyday exchange. Within the United Kingdom, the contention about jurisdiction over time and its measurement was momentarily as live as the wars over space. Brexit is a contention about who has the power to regulate the laws of the geographical unit that is the island of Great Britain, and whether authority may be devolved to a larger political entity. Thus, at least in part, it is a dispute as to whether this administrative authority may be extended in ever finer detail. The measurement of time is an infinite approximation, as knowledge of the movements of the heavenly bodies becomes ever more precise and the ability to time these more exact with finer and more accurate methods.